Enhancing Questioning and Communication Skills in Elementary Science Learning: Challenges and Pedagogical Insights - Fatmawati, Kiki; Muhsinin, Umil; Jati, Mlathi Anggayuh (Al-Bidayah : Jurnal Pendidikan Dasar Islam, 2025)
Education in the 21st century requires students to master higher-order thinking and communication skills to navigate increasingly complex global challenges. In Indonesian primary education, these competencies are emphasized in the Merdeka Curriculum but remain underdeveloped in practice. This study explores the challenges and pedagogical strategies for enhancing questioning and communication skills in elementary science learning. Employing a descriptive qualitative design with a multi-class case study approach, the research was conducted at Madrasah Ibtidaiyah Swasta Nurul Hidayah, Jambi City, involving 24 students and four science teachers purposively selected to represent diverse achievement levels. Data were collected through structured observations, semi-structured interviews, and document analysis, and analyzed using the Miles, Huberman, and Saldaña interactive model with triangulation for validity. The analysis revealed that students’ questioning and communication skills remain basic, constrained by psychological (low self-confidence), pedagogical (teacher-centered instruction), and structural (limited reflective time) factors. Three integrated strategies were identified: (1) question scaffolding to guide students in formulating meaningful questions; (2) dialogic learning environments to encourage open discussion; and (3) authentic assessment and reflective feedback to value students’ inquiry and communication efforts. Fostering these competencies requires a synergistic framework of emotional support, pedagogical scaffolding, and curriculum redesign that strengthens critical thinking and scientific literacy in line with the principles of 21st-century and Merdeka Curriculum education.